Impacto del COVID-19 en la programación radial - Martillo Chonillo, Josué (2022)
The present research aims to analyze the impact of Covid-19 on the TELERADIO and RADIO CENTRO stations in the city of Guayaquil and its impact on the production of their radio programming. To achieve this, a documentary-type investigation was carried out to develop a theoretical framework that serves as a reference for the studies that other people approached on this topic. Subsequently, the work involved a field investigation developed from a mixed approach, since quantitative tools were combined such as the survey applied to a group of radio producers from the stations under study, but a qualitative tool was also applied, such as the interview to six people who work in other stations to have an external opinion on the way they operated at the beginning of the pandemic, and to know what kind of problems they faced and the strategies they used to solve them………